Ovarian cancer recurrence detection may not require in-person physical examination: an MSK team ovary study. Issue 2 (29th December 2021) - Feinberg, Jacqueline; Carthew, Karen; Webster, Emily; Chang, Kaity; McNeil, Nita; Chi, Dennis S; Long Roche, Kara; Gardner, Ginger; Zivanovic, Oliver; Sonoda, Yukio
Abstract : Objective: Given the inconvenience and financial burden of frequent ovarian cancer surveillance and the risks of in-person visits due to COVID-19, which have led to the acceleration of telehealth adaptation, we sought to assess the role of in-person physical examination for the detection of ovarian cancer recurrence among patients enrolled in a routine surveillance program. Methods: This was a retrospective study of patients initially seen from January 2015 to December 2017 who experienced ovarian cancer recurrence during first clinical remission. Descriptive statistics and bivariate analyses were performed to compare differences in detection methods and in patient and disease characteristics. Results: Among 147 patients who met our inclusion criteria, there were no recurrences detected by physical examination alone. Forty-six (31%) patients had recurrence first detected by tumor marker, 81 (55%) by radiographic scan, 17 (12%) by presentation of new symptoms, and 3 (2%) by biopsies taken during non-oncological surgery. One hundred and eleven patients (75%) had multiple positive findings at the time of recurrence. Of all 147 patients, 48 (33%) had symptoms, 21 (14%) had physical examination findings, 106 (72%) had increases in tumor markers, and 141 (96%) had changes on imaging. Conclusions: In-person physical examination was not a primary means of detection for ovarian cancer recurrence for any patient. Substituting in-person visits for virtual visits that include patient-reported symptoms, alongside a regular surveillance protocol that includes tumor marker testing and imaging, may be a suitable approach for the detection of ovarian cancer recurrence while also reducing patient inconvenience and risks to health.